The First Law for the Kerr-Nut Spacetime - Frodden-Cordoba, E (Elsevier B.V., 2022)
We show that the first law for the Kerr-NUT is straightforwardly established with the surface charge method. The entropy is explicitly found as a charge and its value is not proportional to the horizon area. We conclude that there are unavoidable contributions from the Misner strings to the charges, still the mass and angular momentum gets standard values. However, there are no independent charges associated with the Misner strings. © 2022